Co oferuje MIPVU jako metoda identyfikacji metafory? - Marhula, Joanna; Rosiński, Maciej (Polonica, 2017)
The article discusses Metaphor Identification Procedure Vrije Universiteit (known as MIPVU, Steen et al. 2010) as a method that can be systematically applied to localize metaphorical expressions in discourse. Apart from outlining the steps of the procedure, we focus on the theoretical assumptions underlying its origin as well as point at some benefits and difficulties arising during its application to English and Polish data. The primary aim of the article is to present MIPVU as an attempt at creating a reliable and replicable metaphor identification method that can be used in different text types and different languages.